Effects of the Economic Partnership Agreements on Regional Integration in Africa - Awinador-Kanyirige, Darkowa (Department of Commercial Law, 2018)
After gaining independence, African states embraced the idea of regional integration as an approach to boost economic development on the continent. This was evident in the new regional organizations that were predominantly generated among developing states in the southern hemisphere. Majority of these organizations, e.g. Economic Community of West African States (ECOWAS) and Southern African Development Community (SADC), have continuously been striving to deepen social, political and most importantly economic integration and cooperation in Africa. In an attempt to further the regional integration agenda, there have been quite a number of colonial cross-border arrangements with EU. Assessed based on conventional integration theories by scholars like Ernst B. Haas, the prerequisites for effective regional economic integration in Africa, appear to be less successful, juxtaposed with the more developed and economically independent European Union. Although regional organizations like ECOWAS and SADC have managed to establish free trade areas (FTAs), they have failed to attain their agenda of establishing customs unions. Agendas of this kind among other things, are pertinent to consolidating the regional integration process. Even though several issues may be identified as causes of the inefficiency of the integration scheme on the continent, this paper explores the effect of north south trade agreements, in this case the economic partnership agreements (EPAs), on regional integration processes in Africa.